One day estrous cycle shortening induced by antiprogestagen RU486 administration in proestrus to 4-day cyclic rats. (Revista Española de Fisiología, 1995)
Administration of 4 mg of the antiprogestagen RU486 to 4-day cyclic rats in proestrus, which blocks proestrous and diestrous progesterone actions, induced a one day shortening of the ovarian cycle and a reduction of the ovulation rate in the following cycle. These effects were not present when RU486 was administered in estrus or metestrus. RU486 injections either in proestrus or estrus increased the serum levels of LH and 17 beta-estradiol during metestrus. However, only rats injected with RU486 in proestrus presented a 24 hour advancement of the preovulatory surge of gonadotropins and a lack of the LH-inhibiting effect of exogenous estradiol. These results suggest that, in 4-day cyclic rats, the secretion of progesterone by the corpora lutea during diestrous phase retards the follicular development by lowering the serum concentrations of LH, whereas progesterone secretion by the preovulatory follicles in proestrus regulates the estrous cycle length by antagonizing the desensitization of the pituitary to the estrogen negative feedback on LH secretion.